Succession of bacteria communities during production and application of dairy bedding by membrane-covered aerobic fermentation - Yin, Hongjie; Zeng, Jianfei; Fang, Chen; He, Xueqin; Su, Ya; Xiong, Jinpeng; Han, Lujia; Huang, Guangqun (International Journal of Agricultural and Biological Engineering, 2024)
The cost of dairy manure treatment and bedding material purchase increases the operating cost of the dairy farm. Membrane-covered aerobic fermentation system has been widely used for dealing with dairy manure and recycling the final product as bedding material. However, the microbial safety in each processing step is still uncertain. To better understand the bacterial community dynamics during the whole bedding conversion process, a full-chain and large-scale experiment including 16-day membrane-covered aerobic fermentation and 11-day bedding material application was conducted. The results showed that the pile temperatures in the fermentation stage rapidly increased to 80°C and maintained >50°C for more than 11 days and the use of fermentation product as bedding material provided cows with a stable and comfortable bedding environment. The Chao1 and Shannon index decreased at the end of the fermentation stage and remained stable in the application stage, indicating that membrane-covered aerobic fermentation effectively killed some pathogenic bacteria and guaranteed both the maturity and stability of the final product. The dominant bacteria in the fermentation stage were Acinetobacter, Thermus, and Rhodothermus at genus level. Seven common potential pathogens of mastitis (Staphylococcus, Enterococcus, Serratia, Pseudomonas, Corynebacterium, Mycobacterium, and Bacillus) were found at the end of fermentation stage but the relative abundance was low (0.0025%-0.2727%). The dominant bacteria in the application stage mainly included Acinetobacter, Pseudomonas, and Flavobacterium at the genus level. The relative abundance of Pseudomonas increased in the application stage, which was a reminder to the dairy farm to pay attention to the disinfection and timely replacement of bedding material to prevent the occurrence of dairy mastitis. The results of this study contributed deep understanding of the microorganism-driven bedding conversion process and provide practical guidance and cautions for the bedding materials application.Keywords: semi-permeable membrane, dairy manure, aerobic fermentation, bedding material, bacterial diversityDOI: 10.25165/j.ijabe.20241701.8530Citation: Yin H J, Zeng J F, Fang C, He X Q< Su Y, Xiong J P, et al. Succession of bacteria communities during production and application of dairy bedding by membrane-covered aerobic fermentation. Int J Agric & Biol Eng, 2024; 17(1): 232-240.